Congenital pseudarthrosis of the clavicle in a 7-year-old girl: A case report treated with smooth elastic intramedullary pinning without bone grafting and literature review - Ibrahima Farikou; Handy Eone Daniel; Fokam Pius; Nana Chunteng Theophil; Sosso Maurice Aurélien (Open Journal of Orthopedics and Rheumatology - Peertechz Publications, 2017)
Congenital pseudarthrosis of the clavicle is a rare clinical entity. The literature reports to date only 200 clinical cases in the world. The first known description of this pathology dates back to 1910. It is mostly described in girls and often affects the right clavicle. Bilateral, familial forms have been reported. The diagnosis is both clinical and radiological. Concensus is still far from clear to the therapeutic attitude to adopt. We report the case of a 7-year-old girl, the first one encountered in our practice for nearly 20 years, and the second case described in Africa to the best of our knowledge. We treated it surgically with a satisfactory anatomical and functional result.